Authentic relationships in group care for infants and toddlers - resources for infant educarers (RIE) principles into practice - Petrie, Stephanie; Owen, Sue (J. Kingsley Publishers, 2005)
Underpinned by substantive research on meeting the developmental and attachment needs of infants, this book offers constructive advice on how to encourage curiosity, confidence and emotional security in young children. Based on a philosophy of respect and sensitive observation of infants, it is appropriate for use in Sure Start programmes. The contributors offer a model that supports children's development and well being without relying on expensive material resources, and enables a coherent care strategy to be applied across different services. They explain the main elements of the RIE approa.